Stock Market Behavior and Tax Rule Changes: The Case of the Disallowance of Certain Interest Deductions Claimed by Banks - Madeo, Silvia A.; Pincus, Morton (The Accounting Review, 1985)
[The inability to estimate stockholder wealth effect magnitudes and hence disentangle them from changes in the stock market's assessment of the probability that a regulatory change will occur has hampered previous research in the economic consequences of accounting choices. This study measures cash flow effects independent of stock market behavior and thereby permits evidence of significant abnormal return behavior to be used to infer changes in the market's probability assessment of the imposition of a regulatory change. The study uses a seemingly unrelated regressions approach to investigate information events surrounding the issuance of IRS Revenue Procedure 80-55. Issued in late 1980, this rule stated that banks could no longer deduct interest paid on governmental time deposits collateralized by tax-exempt securities. Further, it was to be applied retroactively; and for firms in the sample used in this study, the average estimated tax liability caused by the retroactive provision was $24.2 million, or 5.6 percent of the market value of common stock. In addition to contributing to the economic consequences literature, this study also demonstrates the potential usefulness of capital market data in estimating the magnitude of probability revisions associated with IRS actions. Presumably such evidence is a relevant input in the social choice problem of whether an IRS action has imposed a "substantial impact" on affected parties.]